2018
DOI: 10.3390/biom8030096
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor and Aldosterone-Related Biomarkers of End-Organ Damage in Cardiometabolic Disease

Abstract: The mineralocorticoid receptor (MR) was first identified as a blood pressure regulator, modulating renal sodium handling in response to its principal ligand aldosterone. The mineralocorticoid receptor is also expressed in many tissues other than the kidney, such as adipose tissue, heart and vasculature. Recent studies have shown that MR plays a relevant role in the control of cardiovascular and metabolic function, as well as in adipogenesis. Dysregulation of aldosterone/MR signaling represents an important cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 169 publications
2
16
0
2
Order By: Relevance
“…NK1R antagonists like aprepitant may thus represent a valuable therapeutic option to reduce obesity-and SAS-associated hyperaldosteronism, manage low renin hypertension and limit aldosterone breakthrough. In fact, it is now well demonstrated that aldosterone exerts profibrotic and inflammation actions in the cardiovascular system and kidney, and counteracting its effects has proved its efficacy to reduce the progression of heart failure and chronic nephropathy 36,37 . Especially, NK1R antagonists may constitute an alternative to both mineralocorticoid receptor antagonists whose utilisation is hampered by their antiandrogenic properties 38,39 , and aldosterone synthase inhibitors whose administration leads to accumulation of steroid precursors with mineralocorticoid activity 40 , a phenomenon which may reduce their clinical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…NK1R antagonists like aprepitant may thus represent a valuable therapeutic option to reduce obesity-and SAS-associated hyperaldosteronism, manage low renin hypertension and limit aldosterone breakthrough. In fact, it is now well demonstrated that aldosterone exerts profibrotic and inflammation actions in the cardiovascular system and kidney, and counteracting its effects has proved its efficacy to reduce the progression of heart failure and chronic nephropathy 36,37 . Especially, NK1R antagonists may constitute an alternative to both mineralocorticoid receptor antagonists whose utilisation is hampered by their antiandrogenic properties 38,39 , and aldosterone synthase inhibitors whose administration leads to accumulation of steroid precursors with mineralocorticoid activity 40 , a phenomenon which may reduce their clinical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The RAAS plays a very important role in regulating cardiovascular function, but it may also lead to the occurrence and development of various cardiovascular diseases, including cardiac hypertrophy and heart failure [33,34]. More and more evidence has shown that ALDO plays an important role in the pathological development of cardiovascular disease [33][34][35]. Calvier et al [36] proved that in PAH, ALDO was considered to be a potential tandem biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…В последние годы получены неоспоримые доказательства, что спектр действия альдостерона лежит далеко за пределами узкого перечня «почечных» эффектов. Системная или локальная гиперпродукция гормона вызывает целый ряд патологических реакций [19][20][21][22][23][24]…”
Section: обмен и роль альдостерона в организмеunclassified